A Review on Administrative Justice Competencies in France - Citraresmi Widoretno Putri (Rechtsidee, 2019)
The Indonesian justice system is closer to the French justice system, both general and administrative justice, with its "droits administrative regime". In addition, it is recognized that administrative justice in France is already well-established, so it has become a model for other countries. Therefore, the author tries to conduct normative legal research related to the Absolute Competence of Administrative Justice in France. This is certainly very different from the results of previous research and writings that examine the Study of State Administrative Courts based on the paradigm of Law Number 30 Year 2014 on Government Administration then research on the Absolute Study of State Administrative Courts in the Assessment of the Abuse of Authority, there is also research on Implications of Limiting the Absolute Competence of State Administrative Court, Reformulation of Unlawful Acts by Government Agencies or Officials in the Context of Absolute Competence in State Administrative Court and the Element of Abusing Authority in Corruption Crimes as Absolute Competence of Administrative Justice. The entire previous article is examining the Absolute Competence of Administrative Justice in Indonesia alone and its development while this paper contains the novelty of the elements that examine the history of law relating to the Absolute Competence of Administrative Justice in France. The conclusion is that France adheres to the dualite de la jurisdiction or duality of jurisdiction system. Administrative justice aims and ends at Conseil d'Etat besides general court comes from and aims at the Cour de Cassation (Supreme Court).